What will it take to stabilize the Colorado River? - Wheeler, KG; Udall, B; Wang, J; Kuhn, E; Salehabadi, H; Schmidt, JC (American Association for the Advancement of Science, 2022)
The Colorado River supplies water to more than 40 million inhabitants in the southwestern United States and northwestern Mexico. A basin-wide water supply crisis is occurring because of decreased watershed runoff caused by a warming climate and legal and water management policies that allow systematic overuse. By the end of 2022, combined storage in Lake Powell and Lake Mead, the two largest reservoirs in the United States, will have declined from 95% full in 2000 to approximately 25% full. If this “Millennium Drought” persists, then stabilizing reservoir levels to avoid severe outcomes will require reducing water use to match diminished runoff. With a process underway to renegotiate interstate and international agreements on consumptive uses of the river, we describe a promising new management approach based on combined storage of both reservoirs, rather than just Lake Mead as currently used, to trigger consumptive use reductions to the Lower Basin and Mexico.